Experimental Study on Refuse-Derived Fuel Moisture Content and Gasification Efficiency for Sustainable Energy - Putty Fauthyda Zahra Hapidzha; Damora Rhakasywi; Fahrudin; Regina N. Lumbantoruan; Fazli Iqbal Pasha; M. Reza Marista; Firmansyah (Jurnal ASIIMETRIK Jurnal Ilmiah Rekayasa & Inovasi, 2026)
This study investigates the effect of moisture content in Refuse-Derived Fuel on gasification efficiency at a Waste-to-Energy Power Plant in Surakarta. Using a fixed-bed downdraft gasifier, the research experimentally tests two MC levels of 20% and 50%. High moisture content can absorb significant thermal energy during evaporation, potentially lowering reaction temperatures and syngas quality. The primary objective is to determine the optimal moisture content that maximizes Cold Gas Efficiency and syngas heating value. Results indicate that high feedstock moisture content triggers severe thermal damping within the gasifier core. Parasitic energy consumption for water vaporization significantly suppressed internal bed temperatures (Reactor and Belly zones), thereby chemically quenching primary endothermic carbon-cracking pathways. The mean Cold Gas Efficiency plummeted from an optimized peak of 42.86% in April down to a compromised level of 28.30% in June. These findings provide critical quantitative data and demonstrate that enforcing strict mechanical pre-treatment drying to lock the input moisture threshold near 20% is thermodynamically mandatory to avoid reaction quenching and ensure commercial power-generation viability in tropical climates.